How to empower Grünwald–Letnikov fractional difference equations with available initial condition? - Wei, Yiheng; Cao, Jinde; Li, Chuang; Chen, Yangquan (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, the initial condition independence property of Grünwald–Letnikov fractional difference is revealed for the first time. For example, the solution x(k) of equation aG∇kαx(k) = f(x(k)),  k > a + 1, cannot be calculated with initial condition x(a). First, the initial condition independence property is carefully investigated in both time domain and frequency domain. Afterwards, some possible schemes are formulated to make the considered system connect to initial condition. Armed with this information, the concerned property is examined on three modified Grünwald–Letnikov definitions. Finally, results from illustrative examples demonstrate that the developed schemes are sharp.
Keywords: fractional calculus; independence; initial condition; Grünwald–Letnikov definition; dynamic properties